Peculiarities of neutron scattering by order-disorder antiferroelectrics - Stamenkovic, S. (Condensed Matter Physics, 2002)
Using the dynamical proton (pseudospin)-heavy ion (lattice) model and the
Green function formalism, the effective total differential cross sections for
both coherent and incoherent neutron scattering are derived. The characteristic
interference effects due to both tunnelling of light ions (protons)
and mixed proton-heavy ion scattering processes are expressed by corresponding
pseudospin and pseudospin-phonon form-factors. The scattering
intensity pattern in antiferroelectric phase is accomplished by polar modulation
effects and additional interference in the cross sections. The theoretical
predictions are related to experimental studies of ADP, Rochelle
salt and NaNO₂. Their possible application to test the coexistence of (anti)ferroelectric
and superconducting phases in high-Tc copper-oxide superconductors
is briefly discussed too. З використанням динамічної протон (псевдоспін)-іонної (ґратка) моделі та формалізму функцій Гріна, розраховані ефективні повні диференціальні перерізи для когерентного і некогерентного розсіювання нейтронів. Характерні інтерференційні ефекти, пов’язані як з ту-нелюванням легких іонів (протонів), так і зі змішаними розсіюваль-ними процесами протон-важкий іон, виражені через відповідні псев-доспінові і псевдоспін-фононні форм-фактори. Крім того, загальний вигляд інтенсивності розсіювання вантисегнетоелектричній фазі визначається також ефектами модуляції поляризації та додатковою інтерференцією у перерізах розсіяння. Передбачення теорії обговорюється у зв’язку з експериментальними дослідженнями кристалів ADP, сегнетової солі і NaNO₂. Коротко обговорюється їх можливе застосування для перевірки співіснування (анти)сегнетоелектричної та надпровідної фаз у високотемпературних надпровідниках на основі оксиду міді.